Social and Emotional Learning is a Way to Recover from the Effects of the CORONA Pandemic Shock - Almatari, Ali Said Sulayiam; Almoqbali, Moza Abdullah; Zaid Almaawali, Iman Mohammad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
This study aimed to identify the role of social and emotional learning as a means of recovering from the effects of the Corona pandemic shock, due to the educational, economic, social and health effects of this pandemic, and the study touched on the competencies of social and emotional learning, and some psychosocial support activities include social and emotional learning, logic models for social and emotional learning intervention at the school level, and inclusion of social and emotional learning in the curriculum.